2004
DOI: 10.1093/rpd/nch356
|View full text |Cite
|
Sign up to set email alerts
|

Thermoluminescence dosimetry of a thermal neutron field and comparison with Monte Carlo calculations

Abstract: The characteristics of thermoluminescence dosemeters (TLDs) regarding the determination of photon and neutron absorbed doses were investigated in a thermal neutron beam. Harshaw TLD-100 (LiF:Mg,Ti) and TLD-700 (7LiF:Mg,Ti) were compared with similar materials from Solid Dosimetric Detector and Method Laboratory (People's Republic of China). Harshaw TLD-700H (7LiF:Mg,Cu,P) and aluminium oxide (Al2O3:Mg,Y) from Hungary were also considered for photon dose measurement. The neutron sensitivity of the investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…6×0.125 mm) and TLDs, respectively. TLD-700H and D-3, characterized by a low thermal neutron sensitivity (3.5 mGy/10 10 n th cm −2 ) were used for this purpose (Fernandes et al, 2004;Osvay, 1996). …”
Section: Photon and Mixed-field Irradiationsmentioning
confidence: 99%
“…6×0.125 mm) and TLDs, respectively. TLD-700H and D-3, characterized by a low thermal neutron sensitivity (3.5 mGy/10 10 n th cm −2 ) were used for this purpose (Fernandes et al, 2004;Osvay, 1996). …”
Section: Photon and Mixed-field Irradiationsmentioning
confidence: 99%
“…The Monte Carlo MCNP-4C (10) code was used for a detailed modelling of the fast neutron beam and the thermal column of RPI, employing a source term previously determined using an MCNP model of the reactor core (11) . Beam descriptions and models are reported elsewhere (8,9) . For converting spectra of neutron fluence and photon energy fluence in neutron and photon doses, tabled point-wise kerma factors and energy absorption coefficients were used (12,13) .…”
Section: Methodsmentioning
confidence: 99%
“…This work presents an extensive study on MC radiation transport simulation and TLD for characterising mixed radiation fields occurring in nuclear reactors. The feasibility of these methods is investigated for radiation fields at various locations of the Portuguese Research Reactor (RPI) having distinct dosimetric characteristics-a fast neutron beam with a significant photon dose component (7,8) and a thermal neutron beam having a low photon dose contribution (9) . The performance of the approaches developed in this work is compared with the techniques already existing at RPI, namely the usage of activation foils and ionisation chambers.…”
Section: Introductionmentioning
confidence: 99%
“…These materials were exposed to either gamma, neutron or electron beam irradiation and their use as dosimeters for high and very high radiation dose analyzed [37,38,43,[54][55][56][57]. Neutron detection from a nuclear reactor or neutron sources (such as Am-Be or 252 Cf) using thermoluminescence detectors has been a great challenge in radiation dosimetry, and several works have been devoted to investigating this process in the past [58,[63][64][65][66][67][68][69]. Particularly, interaction of thermal and epithermal neutron with matter has awakened special interest in some authors because a larger effective neutron capture cross-section than fast neutrons is found for some nuclides like 10 B and 6 Li [70][71][72].…”
Section: High and Very-high Radiation Dosementioning
confidence: 99%
“…gives the gamma component and can be used to calculate the thermal neutron response on the other detector [17]. Furthermore, computational tools using the Monte Carlo method were used by some authors to estimate the deposited dose on TL detectors [64,81,82].…”
Section: Detection Of Neutrons In a Nuclear Research Reactormentioning
confidence: 99%